Relationship between urinary metabolites of polycyclic aromatic hydrocarbons and risk of papillary thyroid carcinoma and nodular goiter: A case-control study in non-occupational populations. (15th January 2021) - Liu, Boying; Chen, Yanyan; Li, Siyao; Xu, Yuanyuan; Wang, Yi
Abstract: Exposure to polycyclic aromatic hydrocarbons (PAHs) has been linked to the development of certain diseases. However, the relationship between PAH exposure and thyroid disorders remains unknown. We measured 10 of the most common hydroxylated PAHs (OH-PAHs) in the urine of thyroid nodular goiter (NG) patients, papillary thyroid carcinoma (PTC) patients, and healthy controls by gas chromatography-triple-quadrupole mass spectrometry (GC-MS/MS). We found that the concentrations of 2-hydroxyfluorene (2-OH-FLU), 2-hydroxydibenzofuran (2-OH-DBF), and 1-hydroxyphenanthrene (1-OH-PHE) in the NG group, and of 2-hydroxynaphthalene (2-OH-NAP), 2-OH-DBF, and 1-OH-PHE in the PTC group were significantly higher than those in controls. In addition, participants in the high tertiles of 2-OH-FLU and 1-OH-PHE had higher risk of NG. Besides these two OH-PAHs, elevated risk of NG was observed in women in the high tertiles of 1-hydroxynaphthalene (1-OH-NAP), 2-OH-NAP, 2-OH-DBF, and 3-hydroxyfluorene (3-OH-FLU). Furthermore, participants in the high tertiles of seven OH-PAHs, namely, 1-OH-NAP, 2-OH-NAP, 2-OH-DBF, 2-OH-FLU, 3-OH-FLU, 3/9-hydroxyphenanthrene (3/9-OH-PHE), and 1-OH-PHE, had elevated risk of PTC, and females in these high tertiles had an even higher risk of PTC. Our findings suggest that PAH exposure may increase the risk of NG/PTC, and there may be a gender-specific effect of PAH exposure on the development of NG/PTC. Graphical abstract: Image 1 Highlights: Urinary levels of OH-PAHs in NG/PTC patients were significantly higher than controls. Multiple OH-PAHs were positively associated with the increased risk of NG/PTC. There may be a gender-specific effect of PAH exposure on the development of NG/PTC. OH-PAHs in urine were detected using a sensitive GC-MS/MS method. Abstract : Main finding of the work: PAH exposure was positively associated with the increased risk of NG/PTC, and there may be a gender-specific effect of PAH exposure on the development of NG/PTC.